Milk street. Shorts - Kimball, Christopher; Hirsch, J. M.; Locke, Michelle; Smolin, Ari; Yanagihara, Dawn (Voracious/Little, Brown and Company, 2025)
"In the kitchen, brevity is brilliant. Short recipes are the ones cooks remember best--not only because they're simple to make and easy to repeat, but because they are boiled down to their elemental beauty and charm. In Milk Street Shorts, Christopher Kimball and his team of cooks and editors have developed a repertoire of nearly 150 genius recipes that are casual, improvisational, and fun. These recipes are not just short--they're bolder, better cooking because they're short. Their essential cleverness gives them power that does not require long ingredient lists or all-day cooking. And every recipe packs a punch-throw-it-together meals like "Nothing Soup," Chili Crisp Peanut Noodles, and Five-Ingredient Pork and Kimchi Stew, snacks and side dishes like Sunflower Hummus, Crispy Spiced Chickpeas, and Salt and Vinegar Smashed Potatoes, and smart ways to use your oven, like Reverse-Sear Pork Loin, Skillet Lasagna, and Two-Hour Turkey. Recipes are organized by simplicity--Short, Shorter, and Shortest--with chapters including skillet suppers, sheet-pan traybakes, and weeknight desserts like Clementine Blender Cake." --